Thermoelectric effect on potato tuber (Solanum tuberosum L.) - short communication - Světla Vacková; Josef Vacek (Czech Journal of Food Sciences, 2010)
For scaning rheological properties of tuber tissue during heating, different physical techniques are used. The experiments done on low solids tubers of cv. Magda have shown that maximum thermoelectric effect was obtained at about 60°C in the temperature region where the gelatinisation process of intra-cellular starch starts and some few cell disruptions occur.